2004
DOI: 10.1128/aac.48.12.4745-4753.2004
|View full text |Cite
|
Sign up to set email alerts
|

Oral Activity of a Methylenecyclopropane Analog, Cyclopropavir, in Animal Models for Cytomegalovirus Infections

Abstract: We reported previously that purine 2-(hydroxymethyl)methylenecyclopropane analogs have good activity against cytomegalovirus infection. A second-generation analog, (Z)-9-{[2,2-bis-(hydroxymethyl)cyclopropylidene] methyl}guanine (ZSM-I-62, cyclopropavir [CPV]), has particularly good activity against murine and human cytomegaloviruses (MCMV and HCMV) in vitro. To determine the oral activity of this compound in vivo, BALB/c or severe combined immunodeficient (SCID) mice infected with MCMV and two models using SCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 47 publications
1
56
0
1
Order By: Relevance
“…In other studies of animal models with MCMV or HCMV, CPV was more effective than GCV in reducing MCMV replication in tissues of mice or HCMV replication in human tissue implanted into SCID mice (8). Additional studies were conducted with HCMV to help elucidate the mechanism of action for this compound and to help understand how this compound is so selective for the betaherpesviruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies of animal models with MCMV or HCMV, CPV was more effective than GCV in reducing MCMV replication in tissues of mice or HCMV replication in human tissue implanted into SCID mice (8). Additional studies were conducted with HCMV to help elucidate the mechanism of action for this compound and to help understand how this compound is so selective for the betaherpesviruses.…”
Section: Discussionmentioning
confidence: 99%
“…These analogs had strong antiviral activity against HCMV, murine CMV (MCMV), human herpesvirus 6 (HHV-6), (10,20,24), rat CMV, rhesus monkey CMV, guinea pig CMV (20), and HHV-8 (10). Some of these compounds significantly reduced mortality and virus replication in animal models of HCMV and MCMV (2,8,21). More recently, the second generation of methylenecyclopropane analogs, the 2,2-bis-hydroxymethyl derivatives, were synthesized (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CPV is also active against several HCMV strains that are resistant to GCV or PFA (14). Further experimentation in vivo with CPV demonstrated a 2 to 5 log 10 reduction in titers of murine cytomegalovirus, resulting in reduced mortality in severe combined immunodeficient (SCID) mice and reduced viral replication in human fetal tissue implanted in SCID mice infected with HCMV (15). Toxicology studies performed in vivo demonstrated few to no adverse effects at therapeutic concentrations, making CPV a good clinical candidate for the treatment of systemic HCMV infections (16).…”
mentioning
confidence: 99%
“…Maribavir (MBV) remains experimental after phase III clinical trials showed low toxicity but inadequate antiviral efficacy at the dose tested (2,3). Additionally, methylenecyclopropane nucleoside analogs, such as cyclopropavir (CPV), are being investigated for clinical use (4,5). The CMV UL97 kinase (pUL97) has important roles in the initial phosphorylation of GCV and CPV that is essential for the antiviral activity of these drugs and as a direct antiviral target for the kinase inhibitor MBV, since UL97 shutoff results in severe viral growth impairment in vitro (6).…”
mentioning
confidence: 99%